2008
DOI: 10.1021/jp807022h
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Electronic Structure of [Tetrathiafulvalene]22+ Dimers and Their Long, Intradimer Multicenter Bonding in Solution and the Solid State

Abstract: The long, multicenter bonding in tetrathiafulvalenium cation radical dimers, [TTF](2)(2+), observed in both the solid state and in solution, were computationally investigated via B3LYP, CASSCF(2,2), and MCQDPT/CASSCF(2,2) calculations. The stability of [TTF](2)(2+) dimers originates from [TTF](*+)...anion(-) or [TTF](*+)...solvent electrostatic interactions, whose sum exceeds the [TTF](*+)...[TTF](*+) repulsion, in solution, or the sum of the [TTF](*+)...[TTF](*+) and anion(-)...anion(-) repulsions in solid st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 49 publications
7
70
0
Order By: Relevance
“…Theoretical studies indicated that all [TCNE] 2 2À dimers exhibit long, 2e À /4c (c = center) CÀC bonds, and are prototypes for long, multicenter C À C bonds between radical anions. More recently, long, multicenter C À C bonding has also been observed for [cyanil] 2 2À (2e À /10c (8C + 2O)), [11] [TTF] 2 2 + (TTF = tetrathiafulvalene) (2e À /10c (6C + 4S)), [13] di(2,5,8-tri-tert-butylphenalenyl) (2e À /14c (14C)), [14,15] [tetracyanopyrazine] 2 2À (2e À /8c (8C)), [16] [TCNQ] 2 2À (TCNQ = 7,7,8,8-tetracyano-p-quinodimethane, 2e…”
Section: + a C H T U N G T R E N N U N G [Tcne]mentioning
confidence: 97%
See 1 more Smart Citation
“…Theoretical studies indicated that all [TCNE] 2 2À dimers exhibit long, 2e À /4c (c = center) CÀC bonds, and are prototypes for long, multicenter C À C bonds between radical anions. More recently, long, multicenter C À C bonding has also been observed for [cyanil] 2 2À (2e À /10c (8C + 2O)), [11] [TTF] 2 2 + (TTF = tetrathiafulvalene) (2e À /10c (6C + 4S)), [13] di(2,5,8-tri-tert-butylphenalenyl) (2e À /14c (14C)), [14,15] [tetracyanopyrazine] 2 2À (2e À /8c (8C)), [16] [TCNQ] 2 2À (TCNQ = 7,7,8,8-tetracyano-p-quinodimethane, 2e…”
Section: + a C H T U N G T R E N N U N G [Tcne]mentioning
confidence: 97%
“…Hence, pairs of these TTFs do not resemble previously reported [TTF] 2 2 + dimers. [13] There are essentially no sub van der Waals intrachain TTF···TTF and TCNE···TCNE interactions, but there are 13 C···C, C···S, C···N, and S···N sub van der Waals TTF···TCNE intrachain interactions ( Figure 4, Table 3). The shortest C À C interactions are between TCNE C9 and the equidistant to C3 and C6 atoms of the TTF molecule (3.122 ).…”
Section: Structures Of the Four [Ttf]a C H T U N G T R E N N U N G [Tmentioning
confidence: 99%
“…[18][19][20][21][22][23] In particular, p dimers of oligothiophene radical cations were proposed two decades ago to play a key role in electronic conduction of p-doped polythiophenes. [24] Investigations into the mechanism of the interaction between oligothiophene radical cations [1][2][3][4][5][6][7][8][25][26][27][28][29][30] deepen the understanding of the chemistry of this particularly attractive building block for organic electronics.…”
Section: Introductionmentioning
confidence: 99%
“…This result may indicate that the dimer [ClCNSSS] 2 2+ is, in fact, intrinsically unstable in the gas phase, but in the solid state the overall electrostatic interaction from counter anions compensates the repulsion of two positive charges and makes the aggregate [ClCNSSS] 2 (AsF 6 ) 2 energetically stable. This assumption is supported by the recent analyses of [TTF +• ] 2 [175] and [TCNE −• ] 2 [174,176] dimers by Miller and Novoa, in which closed shell DFT calculations also found a metastable state in the gas phase, while multi-configurational methods indicated an absence of a minimum. The authors note that the stability of these charged dimers originates from cation-anion electrostatic interactions, whose sum exceeds the sum of ion-ion intra-dimeric repulsion in the solid state.…”
Section: Analysis Of Dimerization Process In [Rcnsss] 2 2+mentioning
confidence: 62%